2005
DOI: 10.1097/01.mcg.0000170765.36825.66
|View full text |Cite
|
Sign up to set email alerts
|

Band Ligation Plus Sclerotherapy Versus Sclerotherapy Alone in Children With Extrahepatic Portal Venous Obstruction

Abstract: Although endoscopic band ligation (EVL) plus sclerotherapy (EST) has shown to be superior to any individual method, there is no study in children. We therefore analyzed our experience of EST and EVL + EST in children with extrahepatic portal venous obstruction (EHPVO). Over a period of 8 years, 136 children who presented with a history of recent variceal bleeding due to EHPVO were studied; 30 of them received EVL + EST and 106 received EST alone. In the EVL + EST group, after the first session of EVL, EST was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
2
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 28 publications
(67 reference statements)
1
24
2
1
Order By: Relevance
“…150,151 Band ligation plus sclerotherapy is considered to be better in treating children with chronic PVT than EST alone as it required fewer sessions and fewer complications. 152 Our study has shown that variceal obliteration following endoscopic sclerotherapy opens up spontaneous shunts due to a possible increase in portal pressure in 40% of patients, which in turn protects these patients from further bleeds and recurrence of varices. 153 Patients with chronic portosystemic venous thrombosis have an acceptable long term outcome with 1 and 5 year survival rates of 85.7% and 82.1% respectively.…”
Section: Chronic Portal Vein Thrombosis (Extra Hepatic Portal Venous mentioning
confidence: 72%
“…150,151 Band ligation plus sclerotherapy is considered to be better in treating children with chronic PVT than EST alone as it required fewer sessions and fewer complications. 152 Our study has shown that variceal obliteration following endoscopic sclerotherapy opens up spontaneous shunts due to a possible increase in portal pressure in 40% of patients, which in turn protects these patients from further bleeds and recurrence of varices. 153 Patients with chronic portosystemic venous thrombosis have an acceptable long term outcome with 1 and 5 year survival rates of 85.7% and 82.1% respectively.…”
Section: Chronic Portal Vein Thrombosis (Extra Hepatic Portal Venous mentioning
confidence: 72%
“…Despite the benefits of EVL, risk of variceal recurrence is higher, due to the difficulty of ligating smaller varices in children [8]. Adult studies have shown that EVL followed by low-dose EST is superior to EVL or EST alone, with few variceal recurrences likely due to obliteration of perforating veins and paraesophageal collaterals with EST [8][9][10]. Poddar et al [8] reported their study, the first such study in children, in which they compared combination therapy with sclerotherapy alone.…”
Section: Esophageal Varicesmentioning
confidence: 95%
“…However, band ligation eradicated varices in a significantly shorter time, with fewer treatment sessions, a lower rebleeding rate, and fewer complications when compared with injection sclerotherapy. Despite the benefits of EVL, risk of variceal recurrence is higher, due to the difficulty of ligating smaller varices in children [8]. Adult studies have shown that EVL followed by low-dose EST is superior to EVL or EST alone, with few variceal recurrences likely due to obliteration of perforating veins and paraesophageal collaterals with EST [8][9][10].…”
Section: Esophageal Varicesmentioning
confidence: 97%
“…It reduces the sessions required, complications associated with large-dose EST for initial variceal eradication and the risk of variceal recurrence. Two studies from India supported this combination intervention (Poddar, 2005; Poddar, 2011).…”
Section: Management Of Esophageal Variceal Bleedingmentioning
confidence: 99%